2016
DOI: 10.1007/s40094-016-0225-9
|View full text |Cite
|
Sign up to set email alerts
|

Dyes extracted from Trigonella seeds as photosensitizers for dye-sensitized solar cells

Abstract: In this paper, the extract of Trigonella seeds was used as sensitizer for dye-sensitized solar cells (DSSCs). The natural dye was extracted from the seeds using water and alcohol as solvents for the raw material. The UV-Vis absorption spectra of Trigonella extract solution and dye adsorbed on TiO 2 film were measured. DSSCs sensitized by Trigonella extracted using water as a solvent exhibited better performance with efficiency of 0.215 %. The performance of the fabricated DSSCs was attempted to enhance by acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…They also found that dye consisting of anthocyanin (cyaniding 3‐0‐glucoside) pigment, which has carboxylic groups in the molecule, can adsorb effectively to the surface of TiO 2 . Batniji et al worked on Trigonella used as sensitizers in DSSCs and achieved 0.215% efficiency . Radwan et al found 0.81% efficiency for DSSCs based on natural purple carrot .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They also found that dye consisting of anthocyanin (cyaniding 3‐0‐glucoside) pigment, which has carboxylic groups in the molecule, can adsorb effectively to the surface of TiO 2 . Batniji et al worked on Trigonella used as sensitizers in DSSCs and achieved 0.215% efficiency . Radwan et al found 0.81% efficiency for DSSCs based on natural purple carrot .…”
Section: Introductionmentioning
confidence: 99%
“…Batniji et al worked on Trigonella used as sensitizers in DSSCs and achieved 0.215% efficiency. 21 Radwan et al found 0.81% efficiency for DSSCs based on natural purple carrot. 22 Taya et al employed natural dyes of Safflower, Medicago sativa, and Ros marinus and reached 0.115% efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Of course, in the case of liquid electrolyte use, leakage prevention is very important. Although the power conversion efficiencies are not as significant as those with a liquid-type electrolyte, the higher photovoltage and great transmittance in the visible area present their potential for further modification shortly (Syu et al , 2016; Batniji et al , 2016).…”
Section: Preparation Of Flexible Dye-sensitized Solar Cellsmentioning
confidence: 99%
“…Obviously, synthetic dyes have higher sensitization activity and stability than natural dyes [10,14]. The natural dyes used as sensitizers in DSSCs provide very low efficiencies because of the absence of specific functional attachment groups and low absorption in the visible region of the solar spectrum [54][55][56][57][58]. Zhang et al [59] synthesized three synthetic dyes and studied them by using a TiO 2 photoanode and observed efficiencies as high as 7.6 %, which are higher than those of natural dyes.…”
Section: Photoelectrochemical Characteristics Of Zno Dsscsmentioning
confidence: 99%